2021
DOI: 10.1007/s00392-021-01880-5
|View full text |Cite
|
Sign up to set email alerts
|

Poor humoral and T-cell response to two-dose SARS-CoV-2 messenger RNA vaccine BNT162b2 in cardiothoracic transplant recipients

Abstract: Aims Immunocompromised patients have been excluded from studies of SARS-CoV-2 messenger RNA vaccines. The immune response to vaccines against other infectious agents has been shown to be blunted in such patients. We aimed to analyse the humoral and cellular response to prime-boost vaccination with the BNT162b2 vaccine (Pfizer-BioNTech) in cardiothoracic transplant recipients. Methods and results A total of 50 transplant patients [1–3 years post heart (42),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
128
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(136 citation statements)
references
References 31 publications
6
128
1
1
Order By: Relevance
“…The T-cellular activity was estimated in pre-and post-booster whole blood samples using the Quantiferon SARS-CoV-2 assay (Qiagen, Hilden, Germany [54][55][56] ). In brief, we quantified the interferon (IFN)γ-release after 21-hour incubation of 1 mL heparinized whole blood portions with two different SARS-CoV-2 antigen mixtures (Ag1, Ag2), and with a negative ("Nil") and a mitogen control, using an ELISA (Qiagen).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…The T-cellular activity was estimated in pre-and post-booster whole blood samples using the Quantiferon SARS-CoV-2 assay (Qiagen, Hilden, Germany [54][55][56] ). In brief, we quantified the interferon (IFN)γ-release after 21-hour incubation of 1 mL heparinized whole blood portions with two different SARS-CoV-2 antigen mixtures (Ag1, Ag2), and with a negative ("Nil") and a mitogen control, using an ELISA (Qiagen).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…In contrast, humoral vaccination success (IgG antibodies and neutralizing antibodies) in healthy controls was seen in 49 subjects (98%) after the first vaccine dose, and in 100% after the second vaccine dose [9]. Additionally, healthy controls developed a significantly higher positive T-cell response (interferon-γ release) compared to transplant recipients (80% vs 16%) [9]. It is concluded that the BNT162b2 vaccine does not confer vaccination success against SARS-CoV-2 in the vast majority of cardiothoracic transplant recipients.…”
mentioning
confidence: 88%
“…Antibody titers, functional inhibitory capacity of neutralizing antibodies, and T-cell response (interferon-γ release) were measured via three separate tests. Forty-six (92%) of the transplant recipients did not show any humoral or T-cell response 21 days after completion of the second vaccine dose [9]. In contrast, humoral vaccination success (IgG antibodies and neutralizing antibodies) in healthy controls was seen in 49 subjects (98%) after the first vaccine dose, and in 100% after the second vaccine dose [9].…”
mentioning
confidence: 95%
See 2 more Smart Citations